Examination of the effect of Deep Micro Vibrotactile stimulation on cognitive function for elderly with Alzheimer's Disease - Ayuto Kodama; Yasuhiro Suzuki; Yu Kume; Hidetaka Ota (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2021)
This study aimed to preliminary examine the effect of DMV stimulation on cognitive function in the elderly with moderate dementia. In the single arm study, 5 participants over 85 years old (% female: 100%) with Alzheimer's disease completed treatment of DMV stimulation with 15-40 Hz. 15-40 Hz DMV stimulation was provided during the entire day for 4 weeks. We evaluated therapeutic efficacy on cognitive function including WM, trail making test-part A & part B and the symbol digit substitution task in the participants, comparing outcomes at baseline with those after the 4 weeks intervention. According to statistical analyses, the WM improved significantly after the intervention (p = 0.043), and the others didn't have significant improvement. Our result showed that this DMV stimulation might have potentially positive impact on cognitive memory function in older adults with moderate level of dementia. In conclusion, living environmental intervention utilized 15-40 Hz DMV stimulation can contribute to the new nonpharmacological treatments without invasiveness for the elderly with dementia.